2021
DOI: 10.2147/copd.s287492
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Risk Analysis of Lung Cancer Development in Patients with Chronic Obstructive Pulmonary Disease: Possible Effectiveness of Annual CT-Screening

Abstract: Purpose Lung cancer is a serious complication in patients with chronic obstructive pulmonary disease (COPD) and accounts for approximately 15% of deaths in patients with COPD. However, with the exception of emphysema, few reports to date have been published on the factors that predict lung cancer development in COPD patients. It has been reported that patients with COPD develop lung cancer at a rate of 0.8% - 1.7%/year, but the incidence may be higher in the Japanese population. Therefore, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…A total of 8,254 related studies were retrieved through electronic and manual searching from the initial examination, of which 1,681 duplicates, 6,573 unrelated studies were excluded after reading titles and abstracts. After screening qualified articles by reading the full text, 31 (13,(22)(23)(24)(25)(26) studies were included in the meta-analysis. The study selection process is shown in (Figure 1).…”
Section: Identification Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 8,254 related studies were retrieved through electronic and manual searching from the initial examination, of which 1,681 duplicates, 6,573 unrelated studies were excluded after reading titles and abstracts. After screening qualified articles by reading the full text, 31 (13,(22)(23)(24)(25)(26) studies were included in the meta-analysis. The study selection process is shown in (Figure 1).…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Overall, we included 31studies covering 829,490 patients with COPD, including twenty-one (13,(22)(23)(24)(25)(26)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)) cohort studies, three (27, 49, 50) case-control studies and seven (28, 29, 51-55) cross-sectional studies. These studies were published from 2003 to 2022 with definite diagnostic criteria, and the sample sizes ranged from 198 to 236,494.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations